S127 Gene therapy for alpha-1-antitrypsin deficiency using a pseudotyped lentivirus vector. (12th November 2015) - Paul-Smith, MC; Gelinas, JF; Pytel, K; Chan, M; Meng, C; Cammack, L; Cameron, L; Moran, C; Pringle, I; Davies, L; Inoue, M; Hasegawa, M; et al.
Abstract : Introduction and objectives: A protease/anti-protease imbalance is a characteristic feature of inflammatory lung diseases such as cystic fibrosis (CF) and alpha-1-antitrypsin deficiency related emphysema. A recent trial of alpha-1-antitrypsin (hAAT) enzyme replacement therapy (ERT) suggested that hAAT can slow the progression of lung density loss in alpha-1-antitrypsin deficiency (Chapman et al, Lancet 2015). However, the results are modest and ERT is expensive, so gene therapy may be a more appropriate treatment strategy. The UK Cystic Fibrosis Gene Therapy Consortium has pseudotyped a simian immunodeficiency viral vector with the Sendai virus F and HN proteins (rSIV. F/HN) for efficient transduction of airway epithelial cells. Results: Mice were transduced with rSIV. F/HN-hAAT (1.4e8 TU/mouse) by nasal instillation and culled 10 days post-transduction. hAAT levels in lung tissue homogenate and epithelial lining fluid (ELF) were 3 logs above controls (p < 0.05), and hAAT concentration in ELF was 92 ± 28 μg/ml, similar to the therapeutic hAAT level in ELF of 70 μg/ml (Figure 1 ). For comparison, transfection of mouse lung with cationic lipid GL67A, used in the recent Phase IIb trial of non-viral gene therapy for cystic fibrosis, complexed to plasmids carrying hAAT only led to 0.4 ± 0.1 μg/ml in ELF. A neutrophil elastase (NE) activity assay showed that the recombinant hAAT successfully neutralised NE activity (p < 0.05). In a separate experiment, mice were treated with a single dose of rSIV. F/HN-hAAT (4e7 TU/mouse) and quantification of hAAT one year post-transduction showed that expression was stable over this period. Here, we also demonstrate for the first time that rSIV. F/HN transduction of lung generates significant (p < 0.05) levels of recombinant hAAT protein in serum. Conclusion: In conclusion, rSIV. F/HN produces therapeutically relevant and long-lasting levels of hAAT in murine lung and may offer advantages over enzyme replacement therapy. In addition, we showed that hAAT escapes from the lung into the circulation which may be relevant for a range of diseases including diabetes and graft vs. host disease. Reference: 1 Chapman KR, Burdon JG, Piitulainen E et al. Intravenous augmentation treatment and lung density in severe α1 antitrypsin deficiency (RAPID): a randomised, double-blind, placebo-controlled trial. Lancet . 2015;386 :360–8